PENYULUHAN KEPEMIMPINAN PENDIDIKAN PADA MASA PANDEMI COVID-19 - Agus Fahmi, Haromain, Menik Aryani, dan Baiq Rohiyatun (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2020)
The period of the Covid 19 pandemic has changed the life order of world citizens economically, health, habits, even more specifically in the field of education. Paralysis of teaching and learning activities demands an active role from educational leaders starting at the top level, namely at the policy maker to the level implementing the policy, namely schools. one of the things that can be done is to carry out online or distance learning through an internet online connection. Leadership is a management function to influence, direct, motivate and supervise others in order to carry out planned tasks so as to achieve organizational goals and objectives. The leadership ability or leadership of a manager will greatly affect organizational performance, especially in terms of achieving organizational goals.